Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/23969873221099477
|View full text |Cite
|
Sign up to set email alerts
|

Once versus twice daily direct oral anticoagulants in patients with recent stroke and atrial fibrillation

Abstract: Background: Data on the safety and effectiveness of once-daily (QD) versus twice-daily (BID) direct oral anticoagulants (DOAC) in comparison to vitamin K antagonists (VKA) and to one another in patients with atrial fibrillation (AF) and recent stroke are scarce. Patients and methods: Based on prospectively obtained data from the observational registry Novel-Oral-Anticoagulants-in-Ischemic-Stroke-Patients(NOACISP)-LONGTERM (NCT03826927) from Basel, Switzerland, we compared the occurrence of the primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…We used prospectively collected, individual patient data pooled within an established international collaboration of investigator‐initiated cohort studies of patients with AF and treatment with oral anticoagulants following a recent ischemic stroke or transient ischemic attack (TIA), as described previously. 8 , 14 , 15 , 16 , 17 , 18 This included 3 single‐center (Basel, Switzerland [NOACISP‐LONGTERM; NCT03826927]; 19 , 20 , 21 , 22 Erlangen, Germany; 23 , 24 Verona, Italy 25 ) and 2 multicenter cohorts (CROMIS‐2 [NCT02513316]; 26 , 27 SAMURAI‐NVAF [NCT01581502] 28 , 29 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used prospectively collected, individual patient data pooled within an established international collaboration of investigator‐initiated cohort studies of patients with AF and treatment with oral anticoagulants following a recent ischemic stroke or transient ischemic attack (TIA), as described previously. 8 , 14 , 15 , 16 , 17 , 18 This included 3 single‐center (Basel, Switzerland [NOACISP‐LONGTERM; NCT03826927]; 19 , 20 , 21 , 22 Erlangen, Germany; 23 , 24 Verona, Italy 25 ) and 2 multicenter cohorts (CROMIS‐2 [NCT02513316]; 26 , 27 SAMURAI‐NVAF [NCT01581502] 28 , 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…The time origin for time‐to‐event analyses was the index ischemic event in all patients. We fitted both simple and multivariable models, the latter adjusted for common outcome‐modifying variables (ie, type of index event (stroke vs TIA), age, sex, CHA 2 DS 2 ‐VASc score (without the age and sex components, modified as in prior research 19 , 20 ), type of oral anticoagulation (DOAC or VKA) after index event, time to anticoagulant initiation, dyslipidemia, and eGFR), as in previous studies. 8 , 14 , 15 We imputed missing values in the covariates used in the adjusted models with simple imputation rules (ie, using the median for continuous variables and the mode [most frequent category] for categorical ones), and report the rate of missing values for all variables.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis comparing the efficacy of NOACs versus VKAs within 1 week or within 2 weeks following AIS showed that treatment with NOACs was associated with significantly improved survival and reduced odds of HT and recurrent ischemic stroke compared to VKAs [ 22 ]. Overall benefit over VKAs seems to apply to both once-daily and twice-daily NOACs [ 23 ].…”
Section: Vitamin K Antagonists Versus Non-vitamin K Antagonist Oral A...mentioning
confidence: 99%
“…22 Overall benefit over VKAs seems to apply to both once-daily and twicedaily NOACs. 23 The evolution of guidelines 4 days after mild AIS and small infarct size (lesion ≤1.5 cm), 7 days after moderate stroke and medium infarct size, and 14 days after severe AIS and large infarct size. 10 The same recommendation was included as expert opinion statement in the ESO recommendations for secondary prevention of stroke and other thromboembolic events in patients with stroke or TIA and AF, suggesting antiplatelet therapy in the first 48 hours after AF-associated stroke.…”
Section: Vitamin K Antagonists Versus Non-vitamin K Antagonist Oral A...mentioning
confidence: 99%